Evaluation by M-charts and Microperimeter-MP3 after broad internal limiting membrane peeling for idiopathic epiretinal membrane - Naoto Uchiyama; Tatsuya Jujo; Keiji Sato; Reio Sekine; Kota Kakehashi; Akiko Endo; Yasushi Kitaoka (BMC Ophthalmology)
Abstract Purpose To assess the impact of broad-internal limiting membrane (ILM) peeling on retinal sensitivity (RS) and metamorphopsia assessed using M-CHARTS in patients with idiopathic epiretinal membrane (ERM). Design Retrospective observational case series. Methods The study analyzed 20 eyes treated with broad-ILM peeling within the vascular arcades area for ERM, over a 6-month follow-up. Outcomes measured included best-corrected visual acuity (BCVA), vertical M-CHARTS scores(MV) and horizontal M-CHARTS scores (MV), central macular thickness (CMT), and RS. RS was evaluated using Microperimeter-MP3 at specified central degrees, and points below 10 dB were considered microscotomas (MS). Results Postoperative BCVA improved significantly at 1 month, 3 months, and 6 months(all p < 0.01).No significant changes in CMT were noted.MH score improvements were significant at 6 months (P = 0.03), whereas MV scores remained unchanged (P > 0.05).RS notably improved within the central 4° at 3 months (P = 0.04) and 6 months (P = 0.05), but remained unchanged in the central 10° and 20° regions (P > 0.05). MS did not increase significantly at 1 month postoperatively and remained stable through 3 and 6 months (all P > 0.05). Conclusion Broad ILM peeling suggests potential for improving visual acuity and metamorphopsia in ERM patients without causing long-term detrimental effects on retinal sensitivity or increasing the occurrence of MS.